PENGARUH KOMPENSASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN SANTANA BAKERY PURWODADI - Murtiningsih, Tutik; Sudarmadi, Sudarmadi (STIE Atma Bhakti, 2023)
The purpose of this study is to examine the effect of compensation, motivation and work environment on the performance of Santana Bakery Purwodadi employees. The population and sample in this study were all employees at Santana Bakery Purwodadi with 47 employees. Data collection techniques used in this study were through the dissemination of questionnaires. The data analysis methods used include the analysis of research instruments consisting of validity tests, reliability tests, classical assumption tests, and hypothesis tests. The results of this study show that partial compensation has a positive and significant effect on Employee Performance, motivation has a positive and significant effect on Employee Performance, the work environment has a positive and significant effect on Employee Performance. Simultaneously, the results of compensation, motivation and work environment have a positive and significant effect on the performance of Santana Bakery Purwodadi employees. The results of this study also show that the work environment variable is the most dominant variable in influencing the Performance of Santana Bakery Purwodadi Employees.